ANATOMICAL AND PHYSICAL CHARACTERISTICS OF Cephalostachyum mannii (Gamble) STAPLETON – AN ENDEMIC SCRAMBLING BAMBOO OF NORTHEAST INDIA - Chaman Lal Sharma; Madhubala Sharma; Dahunirikitre M. Lamare; Mahesh Wangkhem; Govinda Pangging (Indonesian Journal of Forestry Research, 2021)
Cephalostachyum mannii is a tall, graceful scandent bamboo with solid culms. It is distributed in Arunachal Pradesh, Meghalaya, Mizoram, and Nagaland states of  Northeast India. The present study was carried out to investigate radial and vertical variations in anatomical and physical properties in the culms of this bamboo species.  The mature culms  (3-4 years old) were selected from forests of  Amkassar Amlarem village, West Jaintia Hills District, Meghalaya, India. The selected internodes of culms were radially divided into outer, middle and inner zones, and vertically bottom, middle and top positions. The vascular bundles were of  Type II and well developed in middle zones of both bottom and middle positions. The number and size of vascular bundles increased from inner to outer zone and decreased from bottom to top. Vessel length and vessel diameter decreased both radially and vertically. Among fibre characteristics, fibre wall thickness increased, while fibre length, fibre diameter, and fibre lumen diameter decreased significantly in both radial and vertical directions.  Among physical properties, density increased, and moisture content decreased in both radial and vertical directions. Radial shrinkage was higher than tangential shrinkage. Both radial and tangential shrinkage decreased significantly from bottom to top. The fibres were long, thick-walled and highly rigid, and the derived indices do not satisfy the requirement as a superior fibrous raw material for pulp and paper making. However, this bamboo species has the potential for making good quality handicrafts and basketry.